2023
DOI: 10.3389/jpps.2023.11136
|View full text |Cite
|
Sign up to set email alerts
|

The role of CYP2C9*2, CYP2C9*3 and VKORC1-1639 variants on the susceptibility of upper gastrointestinal bleeding: A full case-control study

Abstract: Purpose: To investigate whether interindividual variability in the CYP2C9 (*2 and *3 alleles) and VKORC1 (rs9923231) genes is associated with increased risk of upper gastrointestinal bleeding (UGIB) in users of non-steroidal anti-inflammatory drugs (NSAIDs) or low-dose aspirin (LDA).Methods: A full case-control study including 200 cases of patients diagnosed with UGIB and 706 controls was conducted in a Brazilian hospital complex. To perform an analysis of NSAIDs dose-effect, the defined daily dose (DDD) for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Forgerini et al [ 58 ] reported variants in the CYP2C9 gene, as the *2 and *3 alleles are responsible for the slow metabolism of NSAIDs, which increases the risk of gastrointestinal bleeding. Zhou et al [ 59 ] reported pronounced regional differences in the distribution of the CYP2C9*2 and *3 alleles, underscoring the importance of genetic variability in the CYP2C9 gene for the efficacy and safety of drugs on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…Forgerini et al [ 58 ] reported variants in the CYP2C9 gene, as the *2 and *3 alleles are responsible for the slow metabolism of NSAIDs, which increases the risk of gastrointestinal bleeding. Zhou et al [ 59 ] reported pronounced regional differences in the distribution of the CYP2C9*2 and *3 alleles, underscoring the importance of genetic variability in the CYP2C9 gene for the efficacy and safety of drugs on a global scale.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the patient under investigation, ibuprofen was administered at a dosage of 600 mg, resulting in a total daily dose of 1200 mg, which is equal to the established Defned Daily Dose (DDD) for ibuprofen as designated by the World Health Organization [27]. Recent research conducted by Forgerini et al has demonstrated an increased risk of upper GI bleeding in individuals who carry the CYP2C9 * 3 allele and are taking more than 0.5 DDDs of NSAIDs [28]. Considering that our patient was a carrier of the CYP2C9 * 3 allele and utilized ibuprofen at a dose more than 0.5 DDD, it indicates an augmented vulnerability to upper GI bleeding at administrated dosage.…”
Section: Discussionmentioning
confidence: 99%
“…These variants are relatively rare in Iraq, but their impact on ARB therapy should not be overlooked. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%